Rare bird documentation form for Red-necked Phalarope at Union Slough National Wildlife Refuge, 1988 - Dinsmore, Stephen J.et al (1988)
Rare bird documentation form for two Red-necked Phalaropes at Union Slough National Wildlife Refuge in Kossuth County, IA on July 26, 1988. Epson - sheet feed